1997
DOI: 10.1021/jo962402o
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Studies of ω-Cycloheptyl Fatty Acids in Alicyclobacillus cycloheptanicus. Formation of Cycloheptanecarboxylic Acid from Phenylacetic Acid

Abstract: The formation of the structurally novel, mono-substituted cycloheptane ring in omega-cycloheptyl fatty acids in Alicyclobacillus cycloheptanicus (formerly Bacillus cycloheptanicus) has been examined. Feeding experiments with (13)C- and (2)H-labeled intermediates demonstrated that cycloheptanecarboxylic acid (3), probably as its CoA thioester, is the starter unit for omega-cycloheptyl fatty acid biosynthesis. Analysis of the resultant labeling pattern from a feeding experiment with [U-(13)C(6)]glucose suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Astonishingly, the derivative (VII) resembles parts of the unusual predominant eponymous -cycloheptyl fatty acids (XI) from Alicyclobacillus cycloheptanicus (46). The terminal cycloheptane ring is derived from phenylacetate and formed through a so far unknown ring expansion mechanism similar to the production of tropodithietic acid/thiotropocin (46). Possibly all tropone/ tropolone-related compounds found in bacteria may be formed this way either from proffered phenylalanine/phenylacetate (catabolic) or from a C 9 Shikimate pathway intermediate (anabolic).…”
Section: Bacterial Primary and Secondary Metabolites With The Derivatmentioning
confidence: 92%
See 1 more Smart Citation
“…Astonishingly, the derivative (VII) resembles parts of the unusual predominant eponymous -cycloheptyl fatty acids (XI) from Alicyclobacillus cycloheptanicus (46). The terminal cycloheptane ring is derived from phenylacetate and formed through a so far unknown ring expansion mechanism similar to the production of tropodithietic acid/thiotropocin (46). Possibly all tropone/ tropolone-related compounds found in bacteria may be formed this way either from proffered phenylalanine/phenylacetate (catabolic) or from a C 9 Shikimate pathway intermediate (anabolic).…”
Section: Bacterial Primary and Secondary Metabolites With The Derivatmentioning
confidence: 92%
“…Moreover, a very similar sulfur-bridged dicyclic tropolone with broad antibacterial activity spectrum was isolated from Burkholderia cenocepacia (43,44), which can grow on phenylacetate (45). Astonishingly, the derivative (VII) resembles parts of the unusual predominant eponymous -cycloheptyl fatty acids (XI) from Alicyclobacillus cycloheptanicus (46). The terminal cycloheptane ring is derived from phenylacetate and formed through a so far unknown ring expansion mechanism similar to the production of tropodithietic acid/thiotropocin (46).…”
Section: Bacterial Primary and Secondary Metabolites With The Derivatmentioning
confidence: 99%
“…A different mechanism for tropolone ring formation via an epoxide intermediate was confirmed in the degradation of phenylacetyl-CoA, 586 and was proposed in the biosynthesis of omega-cycloheptyl fatty acids. 587 …”
Section: Oxidative Ring Rearrangementmentioning
confidence: 99%
“…The biosynthesis of the cycloheptane ring in 173 (the most abundant fatty acid) has recently been the subject of some very elegant and detailed studies. 66 ]phenylacetic acid) defined the fate of the aromatic hydrogens of phenylacetic acid in the biosynthesis of the cycloheptyl moiety. Incorporation patterns detected by combined use of 2 H NMR and mass spectroscopy following the feeding experiment with l-[ 2 H 5 ]phenylalanine indicated that one quarter of the maximum theoretical deuterium enrichment at C14/17 of 173 is lost during the course of the biosynthesis and moreover, the biosynthetic pathway must proceed through a C 2 symmetrical intermediate in order to account for the observed equal distribution of deuterium between the axial and equatorial positions at the ring methylene carbons.…”
Section: W-cycloheptyl Fatty Acidsmentioning
confidence: 99%